Using Analytical study of the impact of internal factors on the performance of industrial companies - فاروسي, فضيلة; يمن منصور, (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aims to study the internal factors affecting the financial performance of industrial companies, and also through building a model that can evaluate the performance of companies, and indicate the strengths and weaknesses in the performance of industrial companies and what are the factors affecting the performance of industrial companies in Lattakia Governorate after clarifying their importance theoretically, and knowing which of these factors may cause a change in performance. The descriptive analytical approach was applied and a questionnaire was designed directed to employees of industrial companies in Lattakia Governorate aimed at measuring the impact of internal factors on the performance of industrial companies through descriptive analysis of variables and multiple regression, and 526 questionnaires were obtained that can be analyzed. The following results were reached: There is a convergence in the evaluation of the financial performance of industrial companies, as there was a positive evaluation of profitability, liquidity, and financial structure, there is a statistically significant positive effect for each of the company size and production volume and a negative effect of the employee system on profitability, while the administrative style did not have an effect on profitability, and it was proven that there is a statistically significant positive effect for each of the company size and production volume and a negative effect for the employee system and administrative style on liquidity, as well as there is a statistically significant positive effect for each of the company size and production volume and a negative effect for the employee system on the financial structure, while the administrative style did not have an effect on the financial structure.